CA-125, plasma fibrinogen and C-reactive protein in correlation with severity of preeclampsia. - Ibrahem, Wasan W.; Al-Assaly, Raya Kh.; Saeed Al-Haddad, Nada (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Preeclampsia is most common medical disordersduring pregnancy, and the rate of hypertension ranges from 5 – 8 % f or all types of pregnancy. There was a significant difference between cancer antigen -125, plasma fibrinogen and C- reactive protein to the severity of preeclampsia.Objective: To determine the level ofserum CA-125 level, C-reactive protein and plasma fibrinogen in preeclampsia and their association with the severity of disease and progression of mild preeclampsia to severe type.Patients and method: A prospective case-control studywhich was carried out in the department of gynecology and obstetric at Baghdad teaching hospital from 1st ofJanuary 2015 to 1st of July 2015.One hundred forty pregnant women were included; they were selected and divided into three groups:Group A: Thirty five (35) pregnant women with mild preeclampsia.Group B: Thirty five(35) pregnant women with severe preeclampsia.Both group A and B are selected according to the clinical signs, symptoms and investigations and admitted to obstetrics ward for evaluation.Group C: seventy (70) pregnant women with uncomplicated singleton pregnancies as control group .Blood samples were taken for measurement of serum cancer antigen -125, C- reactive protein and plasma fibrinogen for all groupsResults: The mean level of Cancer antigen- 125in control , mild and severe preeclampsia groups was ( 14.4±4.11) , (33.60± 4.52) and ( 37.35± 4.85) respectively which was a significant difference between control ,mild groups ( p value < 0.0001) and between control and severe preeclampsia groups ( p value < 0.0001), the mean level of C-reactive protein in mild and severe preeclampsia was( 15.62± 2.6)and ( 29.3± 7.02) which was significant higher in comparison to control group which was ( 8.17 ± 1.56 ) the P value was < 0.0001 . theplasma fibrinogen levels in mild and sever preeclampsia was (470.37±51.1) and (563.14±48.28) which were markedly higher than that of control group (342. 97±56.6) in third trimester pregnant women.Conclusion:Serum Cancer antigen -125, Serum C - reactive protein and Serum plasma fibrinogen were significantly higher in preeclampsia groups in comparison to the control group and these increments was directly correlated with the severity of preeclampsia .